2017
DOI: 10.1159/000475898
|View full text |Cite
|
Sign up to set email alerts
|

Extinction of Contextual Fear with Timed Exposure to Enriched Environment: A Differential Effect

Abstract: Background: Extinction of fear memory depends on the environmental and emotional cues. Furthermore, consolidation of extinction is also dependent on the environmental exposure. But, the relationship of the time of the exposure to a variety of environmental cues is not well known. The important region involved in facilitation of extinction of fear memory is through diversion of the flow of information leaving the lateral nucleus of amygdala. Purpose: The study aimed to address a question to explain how these br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 64 publications
(63 reference statements)
2
2
0
Order By: Relevance
“…Moreover, the freezing time in rats of the STAND group, in contrast to the animals of the EE group, was approximately the same in the neutral and “dangerous” contexts. Similar data was obtained by Hegde et al (2017) . In their experiments, the rats were trained for CFR in the context of chamber 1, and CFR was tested in the other, albeit very similar context, chamber 2.…”
Section: Enriched Environment and Memorysupporting
confidence: 89%
See 2 more Smart Citations
“…Moreover, the freezing time in rats of the STAND group, in contrast to the animals of the EE group, was approximately the same in the neutral and “dangerous” contexts. Similar data was obtained by Hegde et al (2017) . In their experiments, the rats were trained for CFR in the context of chamber 1, and CFR was tested in the other, albeit very similar context, chamber 2.…”
Section: Enriched Environment and Memorysupporting
confidence: 89%
“…According to our hypothesis, the animals housed in the EE should extinguish the CFR faster than the animals housed in the STAND environment. This was confirmed in many experiments (Hunter, 2015;Lach et al, 2016;Hegde et al, 2017;Cavalcante et al, 2020;on others). In particular, Lach et al (2016) showed that the extinction of CFR in context occurs faster in rats housed in the EE (2 weeks) compared to the STAND group.…”
Section: Extinction Of the Conditioned Fear Reactionsupporting
confidence: 68%
See 1 more Smart Citation
“…Limbic regions including hippocampus and amygdala are involved in the circuitry of contextual fear conditioning (Phillips and LeDoux, 1992 ; Fang et al, 2017 ; Hegde et al, 2017 ) and sensitive to hormonal alterations. THs receptors are rich in both hippocampus and amygdala (Puymirat et al, 1991 ; Desouza et al, 2005 ; Singh et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%